Tailoring cassava starch properties: A study on Heat-Moisture Treatment (HMT) and Annealing (ANN) for enhanced functional applications - Krishna, Y N; Parveen, S; Krishnakumar, T; Anand, M; Gurusamy, K (Plant Science Today, 2025)
Native cassava starch was subjected to HMT and ANN under varying temperature and treatment duration conditions, as designed using a response surface methodology. The physicochemical properties of the modified starch were compared to those of native starch. The two treatments resulted in distinct alterations of the starch properties. HMT and ANN caused changes in solubility, swelling power, pasting properties, freeze-thaw stability, water and oil absorption capacities, water activity, colour and gelatinization characteristics. Solubility increased by 1.4 % and 3.81 % under HMT 25 % and HMT 30 % respectively, whereas ANN at 1: 3 starch-to-water ratio reduced solubility by 4.02 % compared to untreated starch. Swelling power decreased in the modified starch compared to the control sample. Viscosity studies revealed that peak viscosity decreased from 3812 cP in untreated sample to 3267 cP and 3150 cP after HMT - 25 % and HMT - 30 % respectively. In contrast, ANN increased the peak viscosity to 4014 cP. Freeze-thaw stability was narrowed for both HMT and ANN treated starches compared to the untreated starch. The treatments enhanced water absorption capacity but reduced oil absorption capacity (OAC). The clarity of the modified cassava starch pastes slightly decreased compared to the native starch. Moreover, the whiteness of the treated cassava starch powder was marginally lower than that of the untreated starch, though the differences were not statistically significant. These consequences disclosed that HMT and ANN techniques effectively modified the physicochemical properties of cassava starch.